THE SEASONAL TREND OF UPPER-AIR AND VERTICAL TEMPERATURE PROFILE BASED ON RADIOSONDE OVER INDONESIA - Eka Fibriantika; Rahmat Hidayat; Bambang Dwi Dasanto; Yunus Subagyo Swarinoto (Jurnal Sains & Teknologi Modifikasi Cuaca, 2022)
Radiosonde data is one of the data that can be used for upper-air climatological analysis. Pressure, air temperature (T), dew point temperature (Td), wind, and humidity (RH) are the types of data provided by radiosondes. Unfortunately, the utilization of radiosonde data in Indonesia has not been optimal, resulting in a lack of understanding of seasonal air parameter patterns and the vertical structure of the trend of changes in upper-air temperature in Indonesia. This study aims to analyze the seasonal upper-air parameters and analyze the vertical structure of the trend of changes in upper-air temperature in Indonesia. This study uses radiosonde data from 10 radiosonde observation stations in Indonesia. The analysis of seasonal air parameters was carried out by finding the average seasonal value, while the analysis of air temperature trends was carried out using the Mann-Kendall method. The results indicate that the dew point temperature is distinctly different seasonally than the seasonal air temperature. The seasonal dew point temperature difference ranges from 0.5 to 13 oC, while the seasonal air temperature difference ranges from -0.6 to 1.1 oC. The smaller T-Td value, the greater RH value. The trends in upper-air temperature show that most of the study area shows a trend of heating of the upper-air temperature in the troposphere (1000-250 mb), which is between  0.00005 to0.00058 oC/13 years, 0.00012 to 0.00031 oC/9 years, and 0.00009 to 0.00042 oC/10 years and cooling in the lower stratosphere(100 mb) is -0.00011 to -0.00067 oC/13 years.